Influência da fadiga cíclica na resistência à fratura de coroas cimentadas ou parafusadas sobre implante - Valente, Valdimar da Silva (2011)
Background: The aim of the present study was to verify the influence of cyclic fatigue test on the fracture resistance of cement-retained or screw-retained implantsupported single crowns and to evaluate the marginal adaptation of cement-retained single crowns before and after cementation procedure and its influence on strength fractures of the same. Methods: It was used 40 implant-supported single crowns screw-retained (P) and cement-retained (C) modalities, arranged in four groups with ten sample in each category: P1 metal-ceramic screw-retained implant-supported crowns; P2 all-ceramic with zirconia framework screw-retained implant-supported crowns; C1 - metal-ceramic cemented-retained implant-supported crowns; and C2- all-ceramic with alumina framework cement-retained implant-supported crowns. The marginal adaptation before and after cementation were read in microscope with an error of 1μm. The crowns were cemented with zinc phosphate (groups C1 and C2), the bolt were sealed with gutta-percha and composite resin (groups P1 and P2). Half of the samples (n = 20) of all groups were directly submitted to compression fracture (control subgroup), the other half (n = 20) were previously for cyclic fatigue test before compression fracture (experimental subgroup). Fatigue test was 37˚C in distilled water, frequency of 2Hz and 1 million cycles with a load of 0-100N. The mean values presented by the experimental groups (P1E=1.532,51±370,30 Ncm, P2E=1.212,11±188,00 Ncm, C1E=2.394,02±923,70 Ncm e C2E=679,25±59,20 Ncm) were values lower than in control groups (P1C=2.533,23±382,70 Ncm, P2C=1.556,19±383,40 Ncm, C1C=3.361,71±639,60 Ncm e C2C=1.178,12±110,60 Ncm). Marginal gaps of cement-retained implant-supported crowns before cementation (C1=52,65±11,83 μm, C2=85,73±14,06 μm) were lower than after cementation (C1= 66,80±15,86 μm e C2=100,60±38,50 μm). Conclusion: Cyclic fatigue test decreased the fracture toughness of all the crowns on implants tested, independent of fixation type. Cementation procedure interfere with the marginal adaptation of crowns cement-retained implant-supported crowns, the prosthesis with less marginal discrepancy before cementation. Cement-retained implant-supported crown with a smaller marginal gaps offer greater resistance to fracture, independente of material s type it was made.